A Research on TPACK Framework Construction of Teaching Models in the Education of Physical Therapy - Li, Katherine Ning (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Physical therapists must have a rich understanding of medical knowledge, professional skills, and educational background to assist patients in their recovery effectively. However, the academic approach and teaching methods have always been an essential topic in the training of physical therapy professionals. The TPACK framework provides a method for integrating teaching techniques, subject knowledge, and technological applications for professional educators, which can promote more effective educational methods and improve student learning experiences. This study explores constructing and applying a teaching model based on the TPACK framework in physical therapy. By combining technological knowledge, pedagogical knowledge, and content knowledge, this study will examine the value and effectiveness of this teaching model by analyzing real cases and teachers' feedback in the context of physical therapy education. Additionally, we will consider the rapid development of educational technology and future challenges and how to address these challenges to meet the needs of physical therapy education better. Through in-depth research and discussion, this study aims to provide valuable insights and recommendations for education in physical therapy to promote the development of more effective educational models and training methods that better meet patient rehabilitation needs.